A Smart Web Application for Real-Time Indoor Temperature and Humidity Monitoring - Hasbi, M. Hasbi Sidqi Alajuri; Hollanda Arief Kusuma; Marisha Pertiwi; Tonny Suhendra; Gilang Satria Wahyu Dewantara (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Learning comfort is influenced by the environment, including temperature and humidity. This study validates the temperature and humidity monitoring device (DHT 22) in the dashboard system of the Department of Electrical Engineering. The results show high accuracy, with 98.96% for temperature and 98.93% for humidity, and an average error rate of 1.04%. Validation was conducted at BMKG Tanjungpinang for four days, with data recorded every minute for 24 hours. User satisfaction evaluation using the System Usability Scale (SUS) yielded an average score of 57, categorized as